2014
DOI: 10.1109/taslp.2014.2346315
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Speech Detection Using Long-Term Conversational Features for Speaker Diarization in Meeting Room Conversations

Abstract: Abstract-Overlapping speech has been identified as one of the main sources of errors in diarization of meeting room conversations. Therefore, overlap detection has become an important step prior to speaker diarization. Studies on conversational analysis have shown that overlapping speech is more likely to occur at specific parts of a conversation. They have also shown that overlap occurrence is correlated with various conversational features such as speech, silence patterns and speaker turn changes. We use fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The current data segmentation approach makes measuring durations (or frequencies) of overlapping speech difficult. Previous research, however, showed that the number of turn switches is correlated with the number of interrupts and overlaps in a conversation [29,30]. We use this feature as a proxy for the amount of overlapping speech that occurs in a clinical interview.…”
Section: Dialogue Featuresmentioning
confidence: 99%
“…The current data segmentation approach makes measuring durations (or frequencies) of overlapping speech difficult. Previous research, however, showed that the number of turn switches is correlated with the number of interrupts and overlaps in a conversation [29,30]. We use this feature as a proxy for the amount of overlapping speech that occurs in a clinical interview.…”
Section: Dialogue Featuresmentioning
confidence: 99%
“…Overlapping speech occurs when there is more than one speaker speaking at any given instant of time in an audio recording. This is a very common phenomenon in spontaneous conversations like meeting room discussions, telephone conversations, television chat shows, and other similar media . Overlapping speech hinders the performance of speech processing systems such as the HMM based system, in two ways.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. , the authors use features capturing higher level information from structure of a conversation such as silence and speaker change statistics to improve acoustic feature based classifier of overlapping and single‐speaker speech classes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the speaker's voice identification and verification [4,5,6] are becoming attractive features for user-specific services. To provide such services, speaker clustering [7,8] plays a key role in identifying the number of speakers and grouping the utterances from the same user for the automatic user-specific model generation or speaker diarization [9,10].…”
Section: Introductionmentioning
confidence: 99%